Analisis Pemanfaatan Sewa Barang MilikDaerah Pada Kabupaten Boyolali - Yuliani, Yuyun; , Dr. Zulfikar, SE, M.Si (2017)
Regional Property is part of the Local Government assets used or used to support the passage of the duties and functions of the respective government agencies. One form of utilization of the rental by the Indonesian Government Regulation No. 27 of 2014 About the Management of State / Regional Utilization State / Region by the other party within a certain period and receive cash rewards. Department of Revenue, Finance and Regional Property Boyolali Regency is one government agency that acts as the manager of Regional Property to be leased to a third party, lease one source of revenue. The formulation of the issues raised is How the use of the rental property area in Boyolali district which includes the ordinances, the property of the area being leased, the utilization of the lease with the management and the empowerment of traditional markets, the gains DPPKAD Boyolali on the utilization of the rental property area and the accounting treatment for utilization rental property area. The method used in this research is qualitative descriptive method by collecting secondary data and primary data through literature and interviews. After all the data is collected and processed with the analysis, processing and analysis of the data obtained at the same conclusion answer this writing that the increase in revenue from the utilization of Regional Property is renting land and buildings belonging to the Government of Boyolali these indicators in 2015 showed no increase. Obstacles faced in achieving performance targets asset management scope is very broad management and consists of 179 SKPD / UPT and personnel in SKPD very limited.